Dinâmica populacional do sirigado Mycteroperca bonaci e garoupa vermelha Epinephelus morio(TELEOSTEI: EPINEPHELIDAE) capturados no Atlântico Equatorial brasileiro - Ponte, Isabela de Abreu Rodrigues (2022)
Blac k grouper (Mycteroperca bonaci) an d Re d Grouper (Epinephelus morio) ar e large reef fishes that have been subject to intense exploitation by commercial and recreational fisheries. Due to their biological characteristics (e.g. late sexual maturity, low reproductive rate, extensive longevity, and formation of reproductive aggregations), these species become more vulnerable to overfishing. Thus, their IUCN status is nea r endangered spec ies. This thesis was divided into two chapters with unpublished data on population dynamics of two species of groupers caught off the coast of Maranhão and landed in Ceará. The chapters aimed to establish the reproductive, growth and mortality parameters of these two speciesfor management purposes. Data (e. g. biometrics, gonads and otoliths) were sampled monthly, for two consecutive years (2017 and 2018). The total length (cm) and weight (kg) of 137 individuals of M. bonaci and 122 of E. morio were measured, which the minimum and maximum weight and length were 0.976 - 54kg and 44 - 157cm and 1.13 -9.23 kg and 46 - 91cm, respectively. For black grouper the length-weight relationship wasestablished (log (TW) = 11.26 + 3.01log (TL)), growth parameters were obtained using theVon Bertalanffy model (TL∞ (cm): 185.5, k: 0.04, t0 (year): 4.75 (t0 not fixed) and TL∞(cm): 141, k: 0.11 (t0 = 0 fixed)). The highest GSI values and highest frequency of spawning"able to spawn" individuals occurred during the months of June through August, indicatingthe spawning peaks. The estimated total mortality rate (Z) according to the catch-at-agecurve showed a Z value = 0.11 years-1, and the natural mortality was M = 0.04 years-¹. For redgrouperthe total length-weight relationship was established (InWt=3.0308LnTL-11.345),the growthparameters obtained using the Von Bertalanffy model (TL∞ (cm): 92,46, k:0.136, t0 = -2,02). The spawning period corresponded to the dry season in the north of thecountry (Juneto December) and the total mortality was Z = 0.24 years-1 and the naturalmortality was M= 0.12 years-1. It is hoped that through the results obtained, public policiescan be designedto guarantee a sustainable exploitation of these resources.